The formation mechanism of modified thin-film structures based on Ge-Se(S) systems and its influence on physical properties - Horvat, G.T.; Kondratenko, O.S.; Loja, V.Ju.; Myholynets, I.M.; Rosola, I.J.; Jurkovуch, N.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The mechanisms of formation of modified thin-film structures based on GeSe(S)
systems with different Al, Bi, Pb, Te, In modifiers evaporated in vacuum have
been determined. The process of their growth and the structure is greatly influenced by
the vapor composition, energetic state of its particles, the velocity of condensation, the
temperature of the lining and that of evaporator. The 〈Ge₀.₄S₀.₆:Х〉 (Bi,Pb,In),
〈Ge₀.₄S₀.₆:In〉 structure is characterized by the mechanism of condensation which is
realized according to the type: vapor-liquid-solid phase with coalescence. The
condensation mechanism in 〈Ge₀.₄S₀.₆:Al(Te)〉 structures is realized according to the type
vapor-solid phase. The roughness of modified Al (2 аt. %), Bi (14 аt. %), Pb (12 аt. %),
In (1 аt. %, 5 аt. %) structures is 1…13 nm, and for 〈Ge₀.₄S₀.₆:Те〉 (Те is 30.7 аt. %)
structure reaches ~37 nm. The thickness and optical parameters of modified thin-film
structures have been determined using the method of multiangular ellipsometry.